2022
DOI: 10.1017/jfm.2022.255
|View full text |Cite
|
Sign up to set email alerts
|

Repicturing viscoelastic drag-reducing turbulence by introducing dynamics of elasto-inertial turbulence

Abstract: Recently, the nature of viscoelastic drag-reducing turbulence (DRT), especially the maximum drag reduction (MDR) state, has become a focus of controversy. It has long been regarded as polymer-modulated inertial turbulence (IT), but is challenged by the newly proposed concept of elasto-inertial turbulence (EIT). This study is to repicture DRT in parallel plane channels by introducing dynamics of EIT through statistical, structural and budget analysis for a series of flow regimes from the onset of drag reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…This numerical procedure has been fully established for the Newtonian turbulent channel flow by Abe et al [36]. As for the constitutive equations with the Giesekus model, a flux limiter of the MINMOD scheme is adopted to approximate the spatial derivatives in the advective terms; thus, an artificial diffusive term is not included, as first introduced by Yu and Kawaguchi [37] and commonly used even in recent works [38][39][40][41]. The periodic boundary conditions are applied in x and z: u(L x , y, z) = u(0, y, z) and u(x, y, L z ) = u(x, y, 0).…”
Section: Numerical Methods and Proceduresmentioning
confidence: 99%
“…This numerical procedure has been fully established for the Newtonian turbulent channel flow by Abe et al [36]. As for the constitutive equations with the Giesekus model, a flux limiter of the MINMOD scheme is adopted to approximate the spatial derivatives in the advective terms; thus, an artificial diffusive term is not included, as first introduced by Yu and Kawaguchi [37] and commonly used even in recent works [38][39][40][41]. The periodic boundary conditions are applied in x and z: u(L x , y, z) = u(0, y, z) and u(x, y, L z ) = u(x, y, 0).…”
Section: Numerical Methods and Proceduresmentioning
confidence: 99%
“…The above two viewpoints give completely different explanations for the MDR phenomenon, and both of them seem reasonable since the hibernation state and EIT regime all can provide a barrier to prevent laminarization for DRT. In addition, recent studies (Zhu & Xi 2021;Zhang et al 2022) found that the dynamics continue to develop with an increase of Wi even if the flow enters the MDR state. Considering that the MDR limit can be exceeded at low Re (Choueiri et al 2018;Pereira et al 2019), it is very necessary to reexamine the universality of the MDR phenomenon -the same MDR limit for different polymer solution properties.…”
Section: Introductionmentioning
confidence: 95%
“…Through decomposing pressure fluctuations into rapid, slow and polymer parts, Terrapon, Dubief & Soria (2015) confirmed that those small-scale spanwise vortex structures associated with sheets are driven by polymers directly. Recently, we focused on the anisotropy in EIT and pictured the self-sustaining energy process (see Zhang et al 2022). It was found that sheet-like structures in the streamwise direction are caused by the interaction between polymers and turbulent fluctuations, and work done by elastic stress provides energy for their maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations